Single Cell Biology: Exploring Somatic Cell Behaviors, Competition and Selection in Chronic Disease - Zhu, Wandi; Deo, Rahul C.; MacRae, Calum A. (Frontiers in Pharmacology, 2022)
The full range of cell functions is one of the most under-determined aspects of disease biology. The evidence that somatic cell competition and clonal imbalance play a role in non-neoplastic chronic disease reveal a need for a dedicated effort to explore single cell function if we are to understand the mechanisms by which cell population behaviors influence disease. It will be vital to document not only the prevalent pathologic behaviors but also those beneficial functions eliminated or suppressed by competition. An improved mechanistic understanding of the role of somatic cell biology will help to stratify chronic disease, define more precisely at an individual level the role of environmental factors and establish principles for prevention and potential intervention throughout the life course and across the trajectory of wellness to disease.